HIGHLIGHTS OF PATTRU (POULTICE) IN SIDDHA - THANGASWAMY, JENEFA ROSE PRIYA; BALAMURUGAN, MANIKANDAN (International Journal of Ayurveda and Pharma Research, 2018)
Siddha system of medicine is one of the oldest medical system in the world. The treatment in Siddha is made by restoring the original balance of the three vital humours (Vatham, Pitham, Kapham) so that patient becomes healthy. It has a vast number of internal and external therapies. The non-oral therapy is known as External medicines -Pura marundhu.32 types of external applications are mentioned in Siddha. In many instances, only the external procedures without oral intake of drugs are much sufficient. They are quite safe and efficient too. Pattru – Poultice is one among them, used to treat cuts, abscess, furuncles, boils, puffy indurations, haemorrhoids, eczema, etc., as a emollient, fungicidal, germicide and so on... This paper is an attempt to bring out the of analysis of Pattru for various diseases as described in Siddha classical text books along with the mode of action scientifically, so that it would create awareness globally.